1998
DOI: 10.1152/ajpcell.1998.275.2.c599
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ΔF508 CFTR in an epithelial monolayer

Abstract: The ΔF508 mutation leads to retention of cystic fibrosis transmembrane conductance regulator (CFTR) in the endoplasmic reticulum and rapid degradation by the proteasome and other proteolytic systems. In stably transfected LLC-PK1(porcine kidney) epithelial cells, ΔF508 CFTR conforms to this paradigm and is not present at the plasma membrane. When LLC-PK1 cells or human nasal polyp cells derived from a ΔF508 homozygous patient are grown on plastic dishes and treated with an epithelial differentiating agent (DMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 42 publications
2
46
0
Order By: Relevance
“…The dependence of ∆F508 CFTR maturation and targeting upon epithelial polarization has recently been demonstrated in stably transfected cells, as well as in endogenous CFTR-expressing epithelial cells (51,52).…”
Section: Discussionmentioning
confidence: 97%
“…The dependence of ∆F508 CFTR maturation and targeting upon epithelial polarization has recently been demonstrated in stably transfected cells, as well as in endogenous CFTR-expressing epithelial cells (51,52).…”
Section: Discussionmentioning
confidence: 97%
“…Development of novel strategies to stabilize the native ⌬F508 CFTR would complement the present therapeutic approaches aiming to correct the folding defect at the ER, in tissue culture models (10,(22)(23)(24)(25)45), in CF mice (21), and in human trials (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced temperature (10,21,22), chemical chaperones (23)(24)(25), and down-regulation of Hsp70 (26,27) activity are thought to partially revert the folding defect of ⌬F508 CFTR and promote the accumulation of the functional channel at the cell surface. Importantly, using more sensitive electrophysiological techniques, constitutive accumulation of ⌬F508 CFTR was documented in the plasma membrane of primary epithelia from ⌬F508 homozygous mice (21,28) and in the intestinal and gallbladder epithelia of homozygous ⌬F508 patients (29,30).…”
Section: Cystic Fibrosis (Cf)mentioning
confidence: 99%
“…Brown et al showed that glycerol and two other low molecular weight organic compounds, deuterated water and TMAO, mediated increased posttranslational maturation of CFTR⌬F508 in a cell culture model system and this was associated with increased chloride transport activity (14). Other studies have shown that chloride transport is increased significantly by the effect of DMSO (DMSO) on polarized epithelial cell lines expressing CFTR⌬F508 (15). Specific amino acids also appear to affect maturation of CFTR⌬F508 by a chaperone-like mechanism as evidenced by the effect of glutamine in a cell culture model system of CFTR⌬F508 (16).…”
Section: Small Organic Compounds With Chaperone-like Activitiesmentioning
confidence: 99%